Genome-wide mutagenesis and multi-drug resistance in American trypanosomes induced by the front-line drug benznidazole. Issue 1 (December 2017) - Campos, Mônica; Phelan, Jody; Francisco, Amanda; Taylor, Martin; Lewis, Michael; Pain, Arnab; Clark, Taane; Kelly, John
Abstract Chagas disease is caused by the protozoan parasiteTrypanosoma cruzi and affects 5–8 million people in Latin America. Although the nitroheterocyclic compound benznidazole has been the front-line drug for several decades, treatment failures are common. Benznidazole is a pro-drug and is bio-activated within the parasite by the mitochondrial nitroreductase TcNTR-1, leading to the generation of reactive metabolites that have trypanocidal activity. To better assess drug action and resistance, we sequenced the genomes ofT. cruzi Y strain (35.5 Mb) and three benznidazole-resistant clones derived from a single drug-selected population. This revealed the genome-wide accumulation of mutations in the resistant parasites, in addition to variations in DNA copy-number. We observed mutations in DNA repair genes, linked with increased susceptibility to DNA alkylating and inter-strand cross-linking agents. Stop-codon-generating mutations inTcNTR-1 were associated with cross-resistance to other nitroheterocyclic drugs. Unexpectedly, the clones were also highly resistant to the ergosterol biosynthesis inhibitor posaconazole, a drug proposed for use againstT. cruzi infections, in combination with benznidazole. Our findings therefore identify the highly mutagenic activity of benznidazole metabolites inT. cruzi, demonstrate that this can result in multi-drug resistance, and indicate that vigilance will be required if benznidazole is used in combination therapy.